2013
DOI: 10.1097/bot.0b013e3182604b49
|View full text |Cite
|
Sign up to set email alerts
|

Training Femoral Neck Screw Insertion Skills to Surgical Trainees

Abstract: The findings of this study suggest that computer navigation may be safely used to train surgical novices in a basic procedure. This model avoids using both live patients and harmful radiation without a compromise in the acquisition of a 3-dimensional technical skill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…More recent literatures [ 22 , 23 ] have shown the simultaneously expanded feedback offered by the newer technology is likely to be an useful tool to teach surgical techniques and doesn’t do harm to learning. Basing on this presupposition, Leroux et al [ 24 ] conduct a trial to make a comparison on what will the fluoroscopy or electromagnetic (EM) guidance bring to the surgical new hands’ studying about the locking of inserting screw in tibial nails.…”
Section: Discussionmentioning
confidence: 99%
“…More recent literatures [ 22 , 23 ] have shown the simultaneously expanded feedback offered by the newer technology is likely to be an useful tool to teach surgical techniques and doesn’t do harm to learning. Basing on this presupposition, Leroux et al [ 24 ] conduct a trial to make a comparison on what will the fluoroscopy or electromagnetic (EM) guidance bring to the surgical new hands’ studying about the locking of inserting screw in tibial nails.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed to have the potential to improve the precision of guidewire insertion. However, previous studies demonstrated that the navigation system increases the radiation and operative time [1519]. Additionally, the navigation system is expensive and complicated.…”
Section: Discussionmentioning
confidence: 99%
“…10 Computer navigation, which provides concurrent augmented feedback during surgery, has been advocated to be an important surgical training tool in arthroplasty, and potentially in hip fracture surgery as well. 11, 12, 13 Participants who trained with computer navigation took fewer attempts to position screws in the hip and used less fluoroscopy time than those trained with fluoroscopy. 11 …”
Section: Discussionmentioning
confidence: 99%
“…11, 12, 13 Participants who trained with computer navigation took fewer attempts to position screws in the hip and used less fluoroscopy time than those trained with fluoroscopy. 11 …”
Section: Discussionmentioning
confidence: 99%